2018
DOI: 10.11607/ijp.5401
|View full text |Cite
|
Sign up to set email alerts
|

The Effects of Sleeping With or Without Prostheses on Sleep Quality, Sleep Bruxism, and Signs of Obstructive Sleep Apnea Syndrome: A Pilot Study

Abstract: The present results have shown that not wearing a maxillary CD at night is preferable as far as SB and OSAS are concerned, but larger-scale studies are still needed.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(3 citation statements)
references
References 0 publications
0
3
0
Order By: Relevance
“…Utilizing self-reported questionnaires regarding sleep quality and daytime sleepiness (the Pittsburgh Sleep Quality Index, or PSQI, and the Epworth Sleepiness Scale, or ESS), Emami et al [26] found no notable difference in sleep quality or perceived daytime sleepiness in edentulous elderly individuals who either wore or did not wear their dentures at night. In contrast, Mattia et al [27] assessed sleep quality and the presence of sleep apnea in patients using mucosa-supported superior complete dentures and lower implant-retained complete dentures during the nighttime. Consequently, further research employing objective evaluations of sleep disorders within a controlled sleep laboratory setting is recommended to clarify this subject.…”
Section: Discussionmentioning
confidence: 99%
“…Utilizing self-reported questionnaires regarding sleep quality and daytime sleepiness (the Pittsburgh Sleep Quality Index, or PSQI, and the Epworth Sleepiness Scale, or ESS), Emami et al [26] found no notable difference in sleep quality or perceived daytime sleepiness in edentulous elderly individuals who either wore or did not wear their dentures at night. In contrast, Mattia et al [27] assessed sleep quality and the presence of sleep apnea in patients using mucosa-supported superior complete dentures and lower implant-retained complete dentures during the nighttime. Consequently, further research employing objective evaluations of sleep disorders within a controlled sleep laboratory setting is recommended to clarify this subject.…”
Section: Discussionmentioning
confidence: 99%
“…Some authors note that the unstable nature of SB will also be reflected in fluctuations in the result variables of PSG recordings. 49,50 In most studies, SB patients are asked to spend the night in a sleep monitoring laboratory. This action would detract from the validity of the procedure.…”
Section: Discussionmentioning
confidence: 99%
“…In this study, removal of RP and CP during the night was recommended to avoid inflammation of oral mucosa and associated irritations. In this regard, some studies have suggested that wearing complete dentures during sleep has a beneficial effect on sleep complaints ( 18 , 27 ), whereas other studies have found no significant difference between wearing and not wearing complete dentures ( 28 , 29 ). The lack of association in the RP and CP groups with beneficial effect on mean scores of PSQI, ESS and STOP-Bang might be due to the fact that patients were not wearing removable protheses during sleep in this study.…”
Section: Discussionmentioning
confidence: 99%